ANALISIS PROGRAM PEMBERIAN MAKANAN TAMBAHAN (PMT) TERHADAP STATUS GIZI ANAK DI POSYANDU KELURAHAN SEMBUNGHARJO SEMARANG - Nila Wati (TEMATIK: Jurnal Pemikiran dan Penelitian Pendidikan Anak Usia Dini, 2020)
The purpose of this study was to analyze and describe the supplementary feeding program (PMT) on the nutritional status of childrend. Supplementary feeding (PMT) is an important component. This PMT aims to improve the condition of nutritionally vulnerable groups who suffer from malnutrition, especially toddlers. The food ingredients used in PMT should be materials that are locally available or can be produced, so that the possibility of the program being sustainable is greater. Provision of additional food aims to ensure that children always get all types of nutrients needed in appropriate quantities and there is no weight loss. As well as the fulfillment of good nutritional status in children. Nutritional status is also influenced by food intake. Lack of energy consumption can lead to malnutrition and if it continues, it can lead to malnutrition. According to data from the Semarang City Health Office in 2011, the prevalence of malnutrition among children under five was 0.98% and malnutrition was 0.06%. In further analysis, the analysis is additional food with sufficient nutritional content for children, does not contain additional, and an affordable price for the family economy. This research is a descriptive qualitative study. Data analysis was carried out using observation and interviews.